Feasibility of a spinning cylinder on the leading and trailing edges of a flap for high lift - Francannet, Antoine; Prince, Simon A.; Di Pasquale, Davide; Proenca, Anderson R. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
This paper presents a numerical feasibility study of a spinning cylinder mounted on the leading edge and trailing edge of a flap to improve lift force generation. The baseline used in this study is a two-dimensional NLR 7301 airfoil with a single-slotted trailing-edge flap. For this configuration, experimental data is available in the literature. The Ansys computational fluid dynamics (CFD) simulation software has been used in this work to simulate the aerodynamic properties of several configurations. Firstly, a turbulence model dependency study over the existing geometry was conducted, providing lift, drag and pitching moment coefficients, as well as pressure distribution for three angles of attack. Data was then acquired using the Spalart-Allmaras turbulence model at Mach and (chord-based) Reynolds numbers 0.185 and 2.51×10^6, respectively. Three configurations with a leading-edge spinning cylinder and one with a trailing-edge spinning cylinder were investigated. Results suggest that the introduction of a cylinder in the baseline geometry decreased lift and drag performance by inducing flow separation. Nevertheless, for the leading edge configurations, the rotation of the cylinder allowed recovery of the original flapped airfoil performance by re-energizing the flow around the flap and reattaching the boundary layer. For the trailing edge configuration, the spinning cylinder generated additional lift due to Magnus and suction effects at high rotation speed of the cylinder, and by modifying the flow circulation around the flap’s trailing edge. Overall, no benefit over the lift-to-drag ratio could be derived from this preliminary study.